Broadcasting and Development : Options for the World Bank. - Eltzroth, Carter, 1957- (World Bank working paper ;, 2003)
Broadcasting can have a significant part to play in the fight to reduce global poverty. At least 77 percent of the world's population is estimated to be within easy access of broadcast technology (compared to perhaps 4 percent for the Internet), broadcast services are easily accessible by the illiterate and those that speak minority languages. Broadcast operations have been proven sustainable even in low income rural areas. They can play an important role in information transfer (conveying crop prices and employment opportunities, for example). They have played an important role in a range of development projects-including interactive radio instruction, where they have been found to be a highly cost effective intervention. Access to broadcast technologies also has been found to correlate with improved access to government services. Convergence of information and communications technologies (ICT) is allowing broadcast services to be provided over telecommunications networks and Internet services to use broadcast systems. Differentiating broadcast and telecommunications is becoming increasingly anachronistic, many countries are already moving towards a model of convergence regulation that encompasses both sub-sectors. For the World Bank Group to be involved in telecommunications while eschewing broadcast will frequently involve forcing our client countries into suboptimal policy and regulatory solutions. Further, the use of broadcast to provide Internet services is a potential development opportunity that should not be ignored by the Bank in its operations.